2012
DOI: 10.2320/matertrans.m2011345
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Photocatalysis of TiO<sub>2</sub>/ZnO Double-Layer Film Prepared by Pulsed Laser Deposition

Abstract: Nanocrystalline double-layer film of TiO 2 /ZnO was prepared by pulsed laser deposition on quartz substrate and their microstructure, optical property and photocatalysis were investigated. The first/bottom ZnO layer grew on its [001] direction of the wurtzite structure, while the second/top TiO 2 layer consisted of nanorods grown on the [001] direction of its anatase structure. The TiO 2 /ZnO film showed improved photoabsorption in visible light in the UVvisible absorption spectrum; and showed weaken UV emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…The energy band (Eg) gap value of 3.19 eV est for ZnO rods is well within the range reported of ZnO rods prepared by spray pyr which is lower than that of bulk ZnO (3.37 eV at room temperature). This red-shif be probably due to important differences in the surface states [48]. On the other estimated TiO2/ZnO topcoat energy band gap of 3.19 eV was the same as that of ZnO Upadhyay et al produced ZnO:TiO2 nanocomposite powders by the sol-gel meth found the band gaps of the nanocomposite materials in the range of 3.10-3.30 eV [ Figure 5.…”
Section: Uv-visible Spectroscopy (Uv-vis) Measurementmentioning
confidence: 99%
“…The energy band (Eg) gap value of 3.19 eV est for ZnO rods is well within the range reported of ZnO rods prepared by spray pyr which is lower than that of bulk ZnO (3.37 eV at room temperature). This red-shif be probably due to important differences in the surface states [48]. On the other estimated TiO2/ZnO topcoat energy band gap of 3.19 eV was the same as that of ZnO Upadhyay et al produced ZnO:TiO2 nanocomposite powders by the sol-gel meth found the band gaps of the nanocomposite materials in the range of 3.10-3.30 eV [ Figure 5.…”
Section: Uv-visible Spectroscopy (Uv-vis) Measurementmentioning
confidence: 99%
“…Titanium dioxide is non-toxic, chemically stable, earth-abundant and inexpensive, being considered attractive as a photocatalytic material [6]. TiO 2 photocatalytic activity is directly related to size, specific surface area, impurities on crystalline phase, and the exposed surface facets [7], thus several TiO 2 nano/micro structures were reported in order to improve its final performance [7].…”
Section: Tio 2 As a Photocatalyst Materialsmentioning
confidence: 99%
“…TiO 2 has a wide band gap semiconductor material which has been under extensive investigations. This is due to its applications in a variety of fields such as photocatalysis [8], dye synthesized solar cell [9], transient photoconductor [10], and others. In addition, recently, semiconductor-based sensors have drawn intense attention and interest.…”
Section: Introductionmentioning
confidence: 99%